DOES COVID-19 CAUSE STRUCTURAL CHANGES IN THE INDONESIAN STOCK MARKET BEHAVIOR? A COMPARISON OF ISLAMIC AND CONVENTIONAL STOCK - Indri Supriani; Nayaka Artha Wicesa; Yunice Karina Tumewang (Universitas Airlangga, 2024)
Introduction: Islamic stock is believed to be more stable and less risky than conventional stock due to specific screening based on Sharia principles, particularly during economic downturns. This research aims to investigate whether the Covid-19 outbreak caused a structural break in Indonesia's Islamic and conventional stock markets. Methods: This study covers the period from January 2007 to June 2022, divided into sub-periods before Covid-19 (January 2007 to February 2020) and during COVID-19 (March 2020 to June 2022). The study adopts the time series regression method to examine the predicting factors of Islamic and conventional stock indexes, followed by the application of the Chow Breakpoint Test method to determine whether there are structural changes in the Islamic and conventional stock markets due to Covid-19. Results: The results of this study suggest that, in comparison to the period preceding Covid-19, the Islamic stock index demonstrates heightened sensitivity to fluctuations in predicting factors during the pandemic. Additionally, there is an absence of any structural break observed in conventional indices. Consequently, Islamic stocks exhibit lower resistance during crisis periods than conventional stocks. Conclusion and suggestion: This finding prompts a comprehensive evaluation of the Sharia screening standards by policymakers to enhance the resilience of Islamic stocks during economic turmoil. Moreover, based on the results, it is suggested that investors cannot consider the Islamic stock index as a 'safe-haven' instrument during financial turmoil. The result of this research assist investors in adjusting their investment strategies more effectively, particularly in bearish market conditions.